Socialization of Legal Boundaries in Creative Writing for Generation Z Students at SMAN 7 Seluma - Merry Rullyanti; Eli Diana; Aziiz Rahman Putra; Renos Dwi Prawiro; Cici Permatasari (Universitas Dehasen Bengkulu, 2026)
The rapid development of digital technology and social media has encouraged Generation Z to actively engage in creative writing activities across various online platforms. However, limited awareness of legal boundaries in digital content creation may expose students to risks related to copyright infringement, plagiarism, defamation, hate speech, and the dissemination of false information. This community service program aimed to increase students’ understanding of legal aspects in creative writing and to foster responsible content creation practices. The program was conducted at SMAN 7 Seluma, Bengkulu, involving 24 eleventh-grade students. The activities consisted of presentations, interactive discussions, question-and-answer sessions, and practical exercises in creating short creative content using the AIDA (Attention, Interest, Desire, Action) framework. The results showed that participants gained a better understanding of various forms of creative writing, legal regulations related to digital content, and potential legal violations that may occur on social media platforms. In addition, students demonstrated increased awareness of ethical writing practices, respect for intellectual property rights, and the importance of verifying information before publication. Overall, the program successfully enhanced students’ digital legal literacy and encouraged them to produce creative, original, and legally responsible written content. Keywords: creative writing, legal literacy, Generation Z, digital media, community service, social media.